PENGARUH LAYANAN BIMBINGAN KELOMPOK TEKNIK MODELLING DALAM MENGURANGI PERILAKU AGRESIF PADA SISWA SMA NEGERI 1 PANTAI LABU TA. 2025/2026 - Tria Halizah Wulandari; Chairunnisa, Vinda; Sandra Dewi, Ika; Azmi Saragih, Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyse the aggressive behaviour of students in class X of SMA Negeri 1 Pantai Labu Ajaran Year 2025/2026. This research uses a quantitative approach with a type of experimental research (pre-experimental design) through one group pre-test post-test design. The population in the study was 180 students, and the sample was taken by purposive sampling of 10 students who had a high level of aggressive behaviour. The instrument used is a questionnaire, and supported by observation, interview, and documentation. Data analysis was carried out by comparing pre-test and post-test scores to determine the changes in the level of aggressive behaviour after treatment and with the help of the SPSS program version 26.00 for windows. The results of the data analysis in the study showed a significance value (2-tailed) of 0.000 and a t-test value of 8.687, which showed that group guidance services for modelling techniques had a significant effect on the decrease in aggressive behaviour. Thus, it can be concluded that through group guidance services, modelling techniques give influence to students' aggressive behaviour to undergo changes.